Accelerating the monitoring of global biodiversity: Revisiting the sampled approach to generating Red List Indices. Issue 3 (17th February 2020) - Henriques, Sérgio; Böhm, Monika; Collen, Ben; Luedtke, Jennifer; Hoffmann, Michael; Hilton‐Taylor, Craig; Cardoso, Pedro; Butchart, Stuart H. M.; Freeman, Robin
Abstract: Given the current biodiversity crisis, pragmatic approaches to detect global conservation trends across a broad range of taxa are critical. A sampled approach to the Red List Index (RLI) was proposed, as many groups are highly speciose. However, a decade after its conception, the recommended 900 species sample has only been implemented in six groups and trend data are available for none, potentially because this sample is unfeasibly high. Using a broader set of all available data we show that when re‐assessments are conducted every 10 years, 200 species (400 in some cases) should be sufficient to detect a RLI trend. Correctly detecting changes in slope still requires samples of 900 species (11, 000 in some cases). Sampled assessments can accelerate biodiversity monitoring and complement current metrics, but the time‐period between assessments and the approaches' purpose should be carefully considered, as there is a trade‐off between sample size and the resulting indices.